Dropping out: Students’ reasons for leaving their second language teacher education programs at the University of Guanajuato - Houde, Patricia Marie Anne; Geoffrey Richter, Kenneth; Zimányi, Krisztina (Emerging Trends in Education, 2023)
An explanatory case study with the objective of exploring the dropout phenomenon in two undergraduate programs at the University of Guanajuato. It seeks to understand why former students of the Bachelor’s Degree in English Teaching and the Bachelor’s Degree in Spanish Teaching dropped out before finishing their degree. Data collected through the questionnaire are presented, where 53 participants share their experiences of dropping out of school. An explanatory case study is chosen in the methodological design to see how and why dropout occurs. From the responses of the 53 participants, we conducted a deductive-inductive process to code our data from the results of the qualitative survey. The results indicate confirming patterns determined by previous research, citing a combination of personal and institutional causes of dropout. Work obligations, life events, lack of motivation (in terms of loss of interest in the program or profession or vocational disorientation), family situations, administrative problems, mental health, and economic difficulties emerged as key contributing factors in decision making with the potential to change the lives of those involved.